A Systematic Review of Online Peer Assessment Tools for Learning Evaluation - Butarbutar, Ranta; Sauhenda, Angla Florensi; Marnina (Innovare Journal of Education, 2025)
Online peer assessment is a process that uses digital platforms or tools for students to evaluate and provide feedback on their peers’ work. This method aligns with Vygotsky’s sociocultural theory by promoting social interaction, collaborative learning, and the use of technological tools. The purpose of this study was to review the tools used and the lessons learned from online peer assessment (OPA). The literature review identified eight tools that facilitate OPA: (1) Peer Grade (2) Turnitin Peer Mark (3) Eli Review (4) Google Classroom (5) Moodle Workshop (6) Peerceptiv (7) Online Quizzes or Interactive Exercises (8) e-Portfolio. The results show that OPA enhances learning awareness, critical thinking, and metacognitive facilitation and promotes self-regulated learning, inter-professional teamwork, collaboration skills, evaluation skills, diversification feedback, enriches accountability, and actively engages learners. Therefore, it is essential to explore and select a tool that best meets specific needs and requirements, which may necessitate future research.